Benarkah EQ Lebih Penting Daripada IQ? - Putri Lenggo Geni (Humaniora, 2011)
Emotional intelligence has gathered substantial attention from various communities and it is frequently considered as a miracle solution to remedy various psychological and social problems. In educational institutions and organization, general intelligence is still the main predictor in worker or student achievement objective indicators, such as productivity and GPA. These objective indicators is not the only source to measure workers or student or determining their achievements. Emotion is also greatly realted in the goal achievement of the related individual, therefore it is logic to assume that emotional intelligence is one of the factors determining success, performance and an individual’s adaptive behavior